Pengukuran Kandungan Air Tanah di Sekitar Pesisir Kabupaten Situbondo - Wiyono Wiyono (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2020)
Geographical location owned by Situbondo Regency has a coastal area, which could have the potential for sea water intrusion. Therefore, this study aims to explore water resources, namely groundwater in a coastal area of ​​Situbondo Regency - Banyuwangi Regency, which can be used to see the feasibility of life, especially for humans and animals. This research was conducted by sampling groundwater or well water using 3 parameters, namely TDS, pH, and salinity. After measuring the air content using TDS and pH parameters, ground or well water content, it is still suitable for use with a value range of 746 to 1170 mg/L for TDS, and 6.27 to 7.91 for pH content. Meanwhile, the salinity parameter can deny that the area measured in the study experienced sea water intrusion, but the value is not too high, namely 2 to 4 ‰. Then, for future improvements, it is necessary to carry out further research along the road from Situbondo District - Banyuwangi Regency to obtain a broader picture.